Waterloo, Kingman County - Sowers, Megan (Kansas State University, The Chapman Center for Rural Studies, 2016)
Following is a brief but engaging history of the community of Waterloo, Kansas in Galesburg Township of Kingman County and its arboretum that still persists today. This study uses photographs, newspaper articles, maps, and written histories.
Megan Sowers, “Waterloo, Kingman County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/180.
Keywords: Waterloo; Kingman County; Endicott Family; Riggs Arboretum; Lebanon Methodist Church; St. Louis Catholic Church